Smoking Cessation on Periodontal and Peri-Implant Health Status: A Systematic Review - Mario Caggiano; Roberta Gasparro; Francesco D'Ambrosio; Massimo Pisano; Maria Pia Di Palo; Maria Contaldo (MDPI AG, 2022)
Since smoking is considered among the main risk factors for the onset and progression of periodontitis and peri-implantitis, the present systematic review aimed to evaluate the effect of smoking cessation on clinical, radiographic, and gingival crevicular periodontal parameters around natural teeth and dental implants in ex-smokers compared to current and non-smokers. The study protocol was developed based on the PRISMA guidelines, the research question was formulated according to the PICO model, and the literature search was conducted through PubMed/MEDLINE, Cochrane library, and BioMed Central databases. From the 916 title/abstracts initially identified, seven articles were included in the present systematic review and assessed for quality through the ROBINS-I tool. Reported findings on clinical and crevicular periodontal parameters around natural teeth were contrasting when comparing ex-smokers to current and non-smokers; thus, individualized recommendations for previous smoker periodontal patients are currently lacking. No data on radiographic parameters were retrieved. Similarly, data on periodontal parameters around dental implants were not available, highlighting the need for focused investigations assessing the role of both smoking habit and cessation on peri-implant health status and responsiveness to treatment.